(untitled) (Raparin Journal of Humanities (RJH), 2025)
Chomsky’s transformational theory places stress on following a set of transformational rules, such as deletion, movement, addition, and substitution. On the other hand, the techniques of deletion, repetition (addition), fronting, and postponement of sentence components are considered the basics of poetic language. Therefore, there is proximity between transformational rules and the basics of poetic language. In addition, these specific elements are the same that contribute significantly to the formation of rhetorical arts. By embodying these techniques and how or to what extent they are used by the poet’s rubble in his poems, he can develop the style of their formulation and also ensure that they have a more impact on the reader’s mind. This has become a prompt to devote a study on the transformational rules in the poetic text. For this purpose, a collection of modern poems by the well-known Kurdish poet, Moaid Tayyeb, from his collection “Snow, Song and Fire” has been used as a sample for research. The research relied on the components of Chomsky’s transformational theory in addition to the statistical method to extract the percentage of transformational rules used by the poet. The aim of applying these transformational rules to the poetic text is to determine the extent of closeness, similarity, and influence these transformational rules have on enriching the poetic style. It was concluded that the same transformational rules has become the poetic basics of modern poetry, and the amount and manner of using these rules lead to the emergence of poetic styles unique to the poet.